(untitled) (Marketing Journal, 2025)
This article is dedicated to the issues and prospects of improving production efficiency in the construction materials industry. It analyzes the current challenges associated with production processes in this sector and proposes innovative approaches for their effective resolution. The study aims to identify problems, consider possible solutions, and develop practical recommendations aimed at enhancing the production efficiency and competitiveness of enterprises manufacturing modern construction materials.